An Analysis of Four Variants of Splicing Systems - Yuhani, Yusof; Nor Haniza, Sarmin; Fong, Wan Heng; Goode, T. Elizabeth; Muhammad Azrin, Ahmad (American Institute of Physics, 2013)
The theoretical development of splicing system has led to the formulation of new extension of splicing system, namely Yusof-Goode (Y-G) splicing system. This Y-G splicing system, which is associated with Y-G splicing rule, is introduced to show the transparent biological process of DNA splicing. In this paper, a theoretical analysis has been carried out to investigate the similarities and differences between Y-G splicing system with the existing splicing systems namely, Head, Paun and Pixton splicing system in biological point of view.